Quantitative Analysis of Immunoglobulin Subclasses and Subclass Specific Glycosylation by LC-MS-MRM in Liver Disease - Yuan, Wei (J Proteomics, 2015)
Aberrant glycosylation of IgGs has been linked to human diseases, including liver disease. In this study, we have quantified plasma immunoglobulins in cirrhosis (CIR) and hepatocellular carcinoma (HCC) and employed a novel LC-MS-MRM assay to quantify glycoforms of IgG subclasses 1-4. Glycan oxonium ions and peptide-GlcNAc fragment ions were utilized to quantify the IgG glycoforms purified by affinity chromatography with normalization to the unique peptide for each IgG subclass. Our results indicate that HCC patients have increased circulating IgG1, IgG3, IgA1, and IgM compared to healthy controls; comparison of HCC and CIR patients shows that HCC patients have significantly higher concentration of IgG1 and IgM but lower concentration of IgG2. Increase in galactose-deficient core fucosylated glycoforms was consistently observed in CIR and HCC patients. The FA2G0 and FA2BG0 glycoforms increase approximately 2-fold in all IgG subclasses accompanied by a decrease in the FA2G2 glycoform. Fucosylation changes are less pronounced but we have detected increased degree of fucosylation in the IgG1 and IgG3 glycoforms. In conclusion, we have optimized a sensitive and selective LC-MS-MRM method for quantification of immunoglobulin subclasses and their site specific glycoforms, demonstrating that both quantities and glycoforms of immunoglobulins change significantly in liver disease progression to HCC.